Assessing The Effect of Financial Management Behaviors on MSME Revenue Outcomes In Bah Kisat Village - Wico J Tarigan; Mahaitin H Sinaga; Sri Martina (Jurnal Ekuilnomi, 2026)
Financial management practices are widely regarded as a key determinant of microenterprise performance, particularly in developing regions where managerial capabilities often vary across business actors. This study investigates the effect of financial management practices on the revenue performance of Micro, Small, and Medium Enterprises (MSMEs) in Bah Kisat Village, Tanah Jawa District, Indonesia. Using a quantitative research design, data were collected through questionnaires, observations, and interviews from a sample of 54 MSME owners selected using the Slovin formula and convenience sampling. Analytical procedures included validity and reliability testing, assumption testing, multiple linear regression, Pearson product–moment correlation, and hypothesis testing with SPSS Version 25. The empirical findings show that financial management practices do not significantly influence MSME revenue, as indicated by a significance value of 0.414 (> 0.05) and a t-value below the critical threshold (0.824 < 1.675). The Pearson correlation coefficient of 0.114 further demonstrates an absence of meaningful correlation between financial management and revenue performance. These results suggest that financial management practices alone are insufficient to drive revenue growth among MSMEs in this context, implying the presence of other dominant factors such as market access, business scale, digital capability, or competitive dynamics that may better explain variations in revenue. This study contributes empirical evidence to the MSME performance literature by highlighting contextual limitations in the role of financial management within rural microenterprise settings. Future research is encouraged to incorporate additional explanatory variables and comparative regional analyses to deepen understanding of MSME revenue dynamics